The valuation of N-phased investment projects under jump-diffusion processes - Rainer Andergassen; Luigi Sereno (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
In this paper we consider N-phased investment opportunities where the time evolution of the project value follows a jump-diffusion process. An explicit valuation formula is derived under two different scenarios: in the first case we consider fixed and certain investment costs and in the second case we consider cost uncertainty and assume that investment costs follow a jump-diffusion process.
Keywords: G12; G13; G30; C60; 330